2009
DOI: 10.1093/carcin/bgp303
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bladder cancer development by allyl isothiocyanate

Abstract: Bladder cancer is one of the common human cancers and also has a very high recurrence rate. There is a great need for agents capable of inhibiting bladder cancer development and recurrence. Here, we report that allyl isothiocyanate (AITC), an ingredient of many common cruciferous vegetables, potently inhibited the proliferation of bladder carcinoma cell lines in vitro [half maximal inhibitory concentration (IC(50)) of 2.7-3.3 microM], which was associated with profound G(2)/M arrest and apoptosis. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 27 publications
2
62
0
Order By: Relevance
“…flow cytometric analysis and DAPI staining was applied to confirm cell apoptosis in examined GBM 8401 cells. These results corroborate findings of other studies on several different cancer cell lines (34,(36)(37)(38)42). Furthermore, apoptotic cell death is a genetically regulated biological process and it can be divided into extrinsic and intrinsic signaling major pathways (43,44).…”
Section: Discussionsupporting
confidence: 91%
“…flow cytometric analysis and DAPI staining was applied to confirm cell apoptosis in examined GBM 8401 cells. These results corroborate findings of other studies on several different cancer cell lines (34,(36)(37)(38)42). Furthermore, apoptotic cell death is a genetically regulated biological process and it can be divided into extrinsic and intrinsic signaling major pathways (43,44).…”
Section: Discussionsupporting
confidence: 91%
“…As previously mentioned, there are examples showing that different results are observed when the tumor is inoculated subcutaneously or orthotopically in the bladder. In studies of chemoprevention, inhibition of bladder cancer development by allyl isothiocyanate was detected for tumors growing orthotopically but not in the subcutis (Bhattacharya et al, 2010). Furthermore, as described in the previous section, considerable variation has been detected between the two models in assays of immunotherapy, angiogenesis, invasion and metastatic spread, among others.…”
Section: Orthotopic Tumor Growthmentioning
confidence: 93%
“…Studies of carcinogenic substances or prevention of carcinogenesis may be carried out in animal models. Also, analysis of the response to cytotoxicity and immunotherapy treatments can be performed (Bhattacharya et al, 2010;Takeuchi et al, 2011;Zhang et al, 2011). cells are stably transfected with genes coding for fluorescent proteins (Tanaka et al, 2003) or enzymes catalyzing bioluminescence (Hadaschik et al, 2007), allowing for the continuous visualization of tumor development after intravesical instillation of tumor cells.…”
Section: General Characteristics Of Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive epidemiological studies revealed repeatedly an inverse relationship between cruciferous vegetable consumption and the incidence of cancer at a number of sites (Ambrosone et al, 2004;Joseph et al, 2004;Zhao et al, 2007;Lam et al, 2009;Bhattacharya et al, 2010). Isothiocyanates, derived from the hydrolysis of glucosinolates, are believed to mediate the chemopreventive effect of these vegetables.…”
Section: Introductionmentioning
confidence: 99%